Sustainability awareness in engineering design through serious gaming. (18th March 2022) - Scurati, Giulia Wally; Nylander, Johanna Wallin; Ferrise, Francesco; Bertoni, Marco
Abstract: Sustainability considerations are traditionally difficult to trade-off with technical and business requirements in an early design phase. Hence, design teams need support to reflect early on in the process, on how sustainability may affect profitability and customer value fulfilment in the long term. The commoditisation of modelling and simulation techniques points to gamification and serious gaming as emerging approaches to raise awareness among the design team – as well as users and stakeholders – of the expected behaviour of a solution along its life cycle. The objective of this paper is to explore how serious games can be used to inform decision-makers about the value versus cost implications of being (or not being) 'sustainability compliant' when designing products and systems. The paper initially presents the findings from a descriptive study focused on the definition of 'design support' intended to raise sustainability awareness through serious gaming. It further describes the development, application and testing of one of such games for material selection in the aerospace industry.